Arabidopsis G-Protein β Subunit AGB1 Interacts with BES1 to Regulate Brassinosteroid Signaling and Cell Elongation - Zhang, Ting; Xu, Pengbo; Wang, Wenxiu; Wang, Sheng; Caruana, Julie C.; Yang, Hong-Quan; Lian, Hongli (Frontiers in Plant Science, 2018)
In Arabidopsis, brassinosteroids (BR) are major growth-promoting hormones, which integrate with the heterotrimeric guanine nucleotide-binding protein (G-protein) signals and cooperatively modulate cell division and elongation. However, the mechanisms of interaction between BR and G-protein are not well understood. Here, we show that the G-protein β subunit AGB1 directly interacts with the BR transcription factor BES1 in vitro and in vivo. An AGB1-null mutant, agb1-2, displays BR hyposensitivity and brassinazole (BRZ, BR biosynthesis inhibitor) hypersensitivity, which suggests that AGB1 positively mediates the BR signaling pathway. Moreover, we demonstrate that AGB1 synergistically regulates expression of BES1 target genes, including the BR biosynthesis genes CPD and DWF4 and the SAUR family genes required for promoting cell elongation. Further, Western blot analysis of BES1 phosphorylation states indicates that the interaction between AGB1 and BES1 alters the phosphorylation status of BES1 and increases the ratio of dephosphorylated to phosphorylated BES1, which leads to accumulation of dephosphorylated BES1 in the nucleus. Finally, AGB1 promotes BES1 binding to BR target genes and stimulates the transcriptional activity of BES1. Taken together, our results demonstrate that AGB1 positively regulates cell elongation by affecting the phosphorylation status and transcriptional activity of BES1.